Transurethral resection of prostate – a five year experience in College of Medical Sciences and Teaching Hospital,Bharatpur, Nepal - Agarwal, A; Sigdel, G; Lamichhane, N; Belokar, WK (Journal of College of Medical Sciences-Nepal, 2013)
Aims Transurethral resection of prostate(TURP) is still considered gold standard for the management of benign prostatic hyperplasia(BPH) and it has become the need of every urology center today. The purpose of this study is to report a five years experience and results in the management of BPH by TURP. Materials and methods Retrospective analysis of 330 cases of TURP done by single surgeon between January 2007 and December 2011 in urology unit, College of Medical Sciences, Bharatpur, Nepal was carried out. Results Mean age and duration of symptoms was 64.88±3.904 years and 30.7 months respectively , mean size of prostate was 48.33±15.214 grams, mean IPSS before surgery was 27.88±3.493 and after 1 year follow up of 262 cases it was 9.71±3.820. . Mean duration of post operative per urethral catheterization, bladder irrigation with normal saline and total duration of hospital stay was 2.82±0.622, 28.16± 8.895and 3.82±0.622 days respectively. Mean operating time was 40.53±12.949 minutes. 7(2.12%) patients developed intraperitoneal fluid extravasation, 8(2.42%) cases developed clot retention. 2(0.67%) cases re-admitted one week after discharge with clot retention and UTI. 3(0.9%)cases presented two years after surgery with bladder neck contracture. No case of TUR syndrome was seen and there was no mortality. Conclusion Most of the patients presents late with marked obstructive symptoms and large prostate glands in this part of Nepal. The urinary symptoms in patients with BPH significantly improved after TURP and those patients having severe symptoms gained the most. The complication rates following TURP decreases as experience grow and after a experience of 50 TURP they are almost none. So 50 TURP can be set as benchmark for the beginners. It was also noticed that resection volume of the prostate increased and the resection time decreased significantly after 50 case of TURP. Journal of College of Medical Sciences-Nepal, 2012, Vol-8, No-4, 16-21 DOI: http://dx.doi.org/10.3126/jcmsn.v8i4.8695